EVALUASI TERHADAP TENAGA PENDIDIK DAN TENAGA KEPENDIDIKAN DI SMA TUNAS BANGSA KUBU RAYA - sukmawati sukmawati (Jurnal Visi Ilmu Pendidikan, 2020)
AbstrakThis study aims to investigate the implementation of standardized school management using a discrepancy evaluation model at SMA Tunas Bangsa. This article seeks if there are any discrepancies between expectation and reality in implementing standardized school management. Drawing on the descriptive method, data of this study were garnered from interviews, observation, and some related documents. Anchored in Miles and Huberman, The data analysis, based on Miles and Hubermen, consists of three steps: data reduction, data presentation, and conclusion/verification. The findings show that both the teaching staff and the administrative staff fulfill nearly all the required components. This study suggests that either the teaching staff or administrative staff should increase their qualification to postgraduate degrees. All teachers should possess an educator certificate by attending teacher professional training.Keywords: Administrative Staff, Discrepancy, Evaluation, Teaching Staff